Pelatihan Penggunaan Microsoft Office dalam Upaya Peningkatan Pelayanan Administrasi bagi Pegawai Kantor dan Perangkat Desa Rantau Mapesai Kecamatan Rengat Kabupaten Indragiri Hulu - Sri Agustin; Lisa Trisnawati; Sri Guntur (Universitas Pahlawan Tuanku Tambusai, 2022)
In the face of the times, especially the development of increasingly advanced Science and Technology, adequate skills are needed to support the performance of office employees and village officials, especially Rantau Mapesai Village. This is because in service activities to the community, office employees and village officials in Rantau Mapesai are still not optimal in operating Microsoft Office. This condition certainly has an impact on the lack of maximum administrative services to the community. The purpose of this community service is to provide training to improve and maximize the potential of human resources on how to operate computers in Microsoft Word, Microsoft Excel and Microsoft Powerpoint application programs for office employees and village officials. The increase in the average pre-test score of 62.72 to the post-test of 88.00 indicates the level of participants' understanding of Microsoft Office. Through this training activity, participants can understand the importance of using technology in an effort to improve administrative services in the village.